Detention in flagrante delicto and its extension to the perpetrator in the crime of hitman (SCIÉNDO INGENIUM, 2021)
It was investigated when the requirements of personal and temporal immediacy can be extended to the mediate perpetrator, for the arrest in flagrante delicto of the immediate perpetrator, in the crime of hitman in Peru. To achieve the objectives of the investigation, a sample consisting of 14 cases of hit men at the local, national and international level, in the period 2015-2020; as well as statistical information on the alleged causes of the hitman in Peru and its incidence, in the period 2015 - 2017; To obtain information on the study variables, 100 criminal lawyers from Trujillo were considered; The techniques of documentary analysis and the survey were used. The information obtained was statistically processed and the results were discussed with the general methods of Science and particular of Law. It was determined that personal and temporal immediacy, as requirements for the arrest in flagrante delicto of the immediate perpetrator in the crime of hitman, may be extended to the mediate perpetrator when within 48 hours of the preliminary investigation the third assumption of article 446.1.c of Criminal Procedure Code on the evident elements of conviction that have been accumulated in the preliminary proceedings, after the defendant's declaration.